Correlation Between Blood Glucose and Estradiol Levels in Women in Reproductive Age - Lionardi, David; Ginting, Chrismis Novalinda; Chiuman, Linda (Majalah Kedokteran Bandung, 2020)
Type 2 Diabetes mellitus (Type 2 DM) is a metabolic disorder characterized by an increase in blood sugar caused by decreased insulin secretion by pancreatic beta cells and/or impaired insulin function (insulin resistance). This study aimed to determine the specific levels of estradiol hormone in reproductive age women with diabetes mellitus in different age groups. This was an analytical study in September at Royal Prima Hospital, North Sumatra, Indonesia. Twenty women participated in this study after informed consent and were divided into two age groups: 40–45 years old and 46–50 years old. Blood samples were collected after 10-12 hours of fasting to assess blood sugar and estradiol hormone levels. Data were then analyzed using the dependent t-test dependent and compared. No significant difference in blood sugar level was found between the two age groups (p-value=0.113, p-value> 0.05) that there were no significant differences in blood sugar levels between the two age groups. The estradiol hormone level in the age group 40-45 years was lower than in the age group 46–50 years, and the difference was significant (p-value =0.000, p-value<0.05). No significant correlation was seen between type 2 DM and estradiol hormone level in this study. In conclusion, age is not the main contributing factor for the increase and decrease in blood sugar level, and type 2 DM does not correlate with estradiol hormone. Hubungan Antara Kadar Glukosa Darah dengan Kadar Estradiol Pada Masa Reproduktif Diabetes mellitus (DM) Tipe 2 adalah penyakit gangguan metabolik yang ditandai oleh kenaikan gula darah akibat penurunan sekresi insulin oleh sel beta pankreas dan atau ganguan fungsi insulin (resistensi insulin). Penelitian ini bertujuan mengetahui kadar hormon estradiol wanita reproduktif yang menderita diabetes mellitus pada kelompok usia yang berbeda. Penelitian ini merupakan penelitian analitik yang dilakukan di bulan September di Rumah Sakit Royal Prima, North Sumatera, Indonesia. Sebanyak 20 wanita berpartisipasi dalam penelitian ini setelah mendapat persetujuan dan dibagi atas dua kelompok usia, 40–45 tahun dan 46–50 tahun. Sampel darah diambil setelah 10-12 jam puasa untuk menilai kadar gula darah dan hormon estradiol. Data kemudian dianalisis menggunakan t-test dependent dan dibandingkan. Tidak ada perbedaan kadar gula darah yang signifikan antara kedua kelompok usia (p=0.113; p>0.05) sehingga tidak ada perbedaan kadar gula darah yang bermakna antara kedua kelompok tersebut. Kadar hormon estradiol pada kelompok usia 40–45 tahun memiliki kadar estadiol lebih rendah dibanding dengan kelompok usia 46–50 tahun. Tidak terdapat korelasi antara DM tipe 2 dan hormon estradiol yang bermakna pada penelitian ini.. Simpulam, bahwa usia bukan merupakan faktor penyebab utama peningkatan dan penurunan kadar gula darah dan DM tipe 2 tidak berhubungan dengan hormon estradiol.